Effects of Hydrochlorothiazide on Tenofovir Disoproxil Fumarate-Induced Nephrotoxicity in Rats - Iman Ghanim Al-Rakhat (Journal of Global Pharma Technology, 2016)
Background: Tenofovir disoproxil fumarate (TDF), a nucleotide reverse transcriptase inhibitor used for the treatment of hepatitis B virus (HBV) and human immunodeficiency virus (HIV) infections, is now one of the most widely used antiretroviral drug. This is largely due to its high antiretroviral activity, relatively good metabolic profile and more importantly good compliance as it has a once-daily dosing. However, tenofovir disoproxil fumarate can induce renal toxicity which can be attributed to the accumulation of such drug in the proximal renal tubular cells, leading to mitochondrial toxicity, and subsequent renal tubular acidosis leading to acute kidney injury. Objective: This study was designed to investigate whether hydrochlorthiazide has renoprotective effects on tenofovir disoproxil fumarate -induced nephrotoxicity in rats. Methods: Twenty eight healthy adult male albino rats weighing 180-200g were utilized in this study. Rats were randomly divided into four groups (7animals each). Group I: Negative control (given distilled water) orally by gavage tube for 5 weeks; Group II: Rats orally received 600 mg/kg/day tenofovir disoproxil fumarate by gavage tube for 5 weeks; Group III: Rats administered hydrochlorothiazide alone at a dose (10 mg/kg/day) by gavage tube for 5 weeks and Group IV: Rats administered hydrochlorothiazide at a dose (10 mg/kg/day) plus tenofovir disoproxil fumarate 600 mg/kg/day by gavage tube for 5 weeks. Results: Administration of hydrochlorothiazide plus tenofovir disoproxil fumarate to rats for 5 weeks produced significant elevation (P<0.05) of MDA content and a significant reduction (P<0.05) in the total antioxidant level in renal homogenate compared to the corresponding levels of negative control animals. Conclusion: treatment with hydrochlorothiazide plus tenofovir disoproxil fumarate in an attempt to prevent the renal toxicity-induced by tenofovir disoproxil fumarate is not effective for inhibiting oxidative stress process.